(untitled) (Research, Society and Development, 2025)
Among the possible mechanisms, the stimulation of pancreatic cells and ductal proliferation stand out, but confounding factors such as a previous history of pancreatitis, hypertriglyceridemia, and alcohol use make definitive conclusions difficult. Given this scenario, caution is recommended when prescribing to patients at high risk, in addition to strict monitoring of symptoms such as severe abdominal pain, nausea, and vomiting. Early detection and discontinuation of the drug in case of suspicion are essential to prevent complications. It is concluded that, despite being effective in glycemic control and weight loss, Ozempic and Mounjaro require continuous clinical monitoring and further studies to clarify their relationship with acute pancreatitis. Among the possible mechanisms, the stimulation of pancreatic cells and ductal proliferation stand out, but confounding factors such as a previous history of pancreatitis, hypertriglyceridemia, and alcohol use make definitive conclusions difficult. Given this scenario, caution is recommended when prescribing to patients at high risk, in addition to strict monitoring of symptoms such as severe abdominal pain, nausea, and vomiting. Early detection and discontinuation of the drug in case of suspicion are essential to prevent complications. It is concluded that, despite being effective in glycemic control and weight loss, Ozempic and Mounjaro require continuous clinical monitoring and further studies to clarify their relationship with acute pancreatitis.